2011
DOI: 10.1080/00346764.2011.563507
|View full text |Cite
|
Sign up to set email alerts
|

Working Hours and Sustainable Development

Abstract: Many works on sustainable development stress the part played by reduced working hours in the promotion of a model for alternative development. The direct link between working hours and the environment, however, still deserves to be supported. This is the issue we would like to discuss through an analysis of the relationships between consumption and working hours. We use surveys on French household expenses to highlight the environmental consequences of long hours: they encourage goods and energy-intensive cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 54 publications
1
24
0
Order By: Relevance
“…Rosnick and Weisbrot (2007) demonstrate that if European countries adopted a US pattern of work and leisure-time distribution they would likely increase their energy consumption by around a quarter. And, a micro-level study of the relationship between working hours and environmental impact in French households revealed that long working hours are positively correlated with affluent consumption and high impact behaviour (Devetter and Rousseau, 2011). Similar results are found by Pullinger (2011) in a comparative study of the UK and the Netherlands in an analysis which accounts for external as well as personal differences between households.…”
Section: Work Time and Environmental Impactsupporting
confidence: 73%
“…Rosnick and Weisbrot (2007) demonstrate that if European countries adopted a US pattern of work and leisure-time distribution they would likely increase their energy consumption by around a quarter. And, a micro-level study of the relationship between working hours and environmental impact in French households revealed that long working hours are positively correlated with affluent consumption and high impact behaviour (Devetter and Rousseau, 2011). Similar results are found by Pullinger (2011) in a comparative study of the UK and the Netherlands in an analysis which accounts for external as well as personal differences between households.…”
Section: Work Time and Environmental Impactsupporting
confidence: 73%
“…The answer depends on changes of income and of the composition of consumption. Assuming a salary cut that is proportional to the reduction of working hours, the effect of reduced consumption is found to be significantly stronger than the effect of a potential shift towards more resource intensive consumption (Devetter and Rousseau, 2011;Nässén and Larsson, 2015;Pullinger, 2011). In other words, emission reductions and broader environmental benefits look possible.…”
Section: Post-growth Strategies Can Be More Feasible Than Techno-fixementioning
confidence: 97%
“…In contrast, a French study finds that households with longer hours of work have higher impact through bigger homes, more transport expenditures and higher expenditures for eating out. (Devetter and Rousseau 2011).…”
Section: Previous Researchmentioning
confidence: 99%